"Once an Eagle, always an Eagle?": symbolic divestment, recuperative critique, and in-house protests against the anti-gay BSA. Issue 1 (2nd January 2017) - Houdek, Matthew
ABSTRACT: A group of Eagle Scouts protested the Boy Scouts of America's (BSA) anti-gay, lesbian, bi-sexual, and queer policies and heteronormative citizenship ideals by forfeiting their badges, divesting their membership, and writing personal, emotionally charged letters addressed to the BSA to critique the institution from within. Engaging the correspondence illuminates the repertoires of critique and dissent they employ in their in-house protests. To these ends, this essay makes four primary contributions: it (re)calls attention to the correspondence archive as a fruitful site to investigate political speech acts and forms of dissent; it provides an understanding of the politics of emotions in protest and social change efforts, thus contributing to resonant dialogues in social movement studies; it codifies the Eagle Scouts' particular tactics employed in their in-house protests, captured in the terms "symbolic divestment" and "recuperative critique"; and it offers a case study that details the rhetorical mechanisms of intrainstitutional change.